Upaya Guru PAI dalam Mewujudkan Visi dan Misi MA Manbaul Hikam Tegalmojo - Muhammad Ilyas (LP3M Universitas Islam Zainul Hasan Genggong, 2015)
This research has an objective to know 1) implementation of perspective and mission of effort of PAI (Pendidikan Agama Islam) teacher in creating perspective and mission of MA Manbaul Hikam Tegalmojo in teaching learning process (Kegiatan Belajar Mengajar). 20 the effort of PAI teacher in creating perspective and mission of PAI teacher in creating perspective and mission of MA Manbaul Hikam Tegalmojo. The research method which is used in this research is qualitative descriptive. The data which have been collected is analyzed use deductive approach. The result of this research shows that the process if teaching learning process in efforts of PAI teacher in creating the perspective of mission of MA. Manbaul Hikam Tegalmojo have used KTSP curriculum. Then, the implementation of efforts of PAI teacher in creating the perspective of mission of MA Manbaul Hikam Tegalmojo is through muatan local, extracurricular and students coaching skill. Then, the program intra curricular is done through the organization of teaching learning process that consist of the mastering of material, mastering of lesson, knowing the personality of students and teaching learning process and giving assessment and evaluating. In teaching learning process, there is a teacher who still cannot understand the perspective and mission of Madrasah, cannot use the method and media that is appropriate with given material. The efforts of PAI teacher in creating the perspective of mission of MA Manbaul Hikam Tegalmojo has role to arrange the perspective and mission of Madrasah, identify the need of Pendidikan agama islam, arrange the lesson plan, and do the comparison with more progressive school, make the religiosities extracurricular to improve the quality of science and worship. Teacher of PAI also evaluate about the achievement of student in material of PAI and also teacher of PAI evaluate the barrier in learning and try to solve it. The barrier that is found by teacher is cannot understand comprehensively the curriculum KTSP, also from the financial which cannot support the qualified teaching learning.